Культурный слой поселения Анетовка 2 на примере северо-восточного производственного участка - Главенчук, А.В. (Материалы по археологии Северного Причерноморья, 2019)
Archaeological material is present at the site in all lithological levels of Late Pleistocene and Holocene age, the main part of cultural layer (40 50 cm thick) and is located in yellow deluvial loamy soil in vertically suspended condition. Archaeological objects of Anetovka 2 experienced the impact of various natural factors such as atmospheric precipitation, weathering, plant growing processes, animal activity, that led to partial ruining and horizontal dislocation of cultural layer, though the main part of it is located in situ. Archaeological objects of large size such as big stones, faunal remains etc. formed significant assemblages that mark places of stone / bone tools production, animal carcasses procession and ritual activity. These objects experienced the least displacement and their location indicates the ancient site surface.